The Reformations in Britain, 1520-1603 - French, Anna, author.
1 online resource.
Keywords: "This entirely fresh narrative of the "British Reformations" focuses on the emotional as well as the material experience of living through the reformations in Britain during the sixteenth century. Aided by a Who's Who and Chronology, The Reformations in Britain is an invaluable resource for all students who study the religious and cultural history of sixteenth-century Britain"--